The age-related changes of dietary phosphate responsiveness in plasma 1,25-dihydroxyvitamin D levels and renal Cyp27b1 and Cyp24a1 gene expression is associated with renal α-Klotho gene expression in mice - Yoshikawa, Ryouhei (J Clin Biochem Nutr, 2018)
In this study, we investigated the relationship between age-related changes in renal α-Klotho gene expression, vitamin D metabolism and the responsiveness of dietary phosphate in 1, 2 and 13 month-old mice fed a high phosphate (phosphate 1.2%) diet or low phosphate (phosphate 0.02%) diet for 5 days. We found that 1,25-dihydroxyvitamin D levels in plasma were significantly lower in the high phosphate group than the low phosphate group for 1 and 2 month-old mice, but not 13 month-old mice. In addition, in the high phosphate group plasma 1,25-dihydroxyvitamin D levels were decreased in 2 month-old mice relative to 1 month-old mice, but 13 month-old mice had higher levels than 2 month-old mice. In fact, plasma 1,25-dihydroxyvitamin D levels showed a significant correlation with vitamin D metabolism gene Cyp27b1 and Cyp24a1 mRNA expression in the high phosphate group. Interestingly, renal α-Klotho mRNA and protein levels were significant change with age. Furthermore, α-Klotho mRNA expression showed a significant negative correlation with plasma 1,25-dihydroxyvitamin D levels in the high phosphate group. Our results suggest that age-related alterations in renal α-Klotho expression could affect the responsiveness of dietary phosphate to vitamin D metabolism.